How do we prove this expression?

x>0, y>0, z>0

x/y + y/z >= 2

I tried expanding, xz + y^2 >= 2yz

I see that if x = z, this expression is true, from x^2 + y^2 >= 2xy,

but how do we phrase that?

Printable View

- Oct 7th 2010, 11:38 PMLukybearInequalities
How do we prove this expression?

x>0, y>0, z>0

x/y + y/z >= 2

I tried expanding, xz + y^2 >= 2yz

I see that if x = z, this expression is true, from x^2 + y^2 >= 2xy,

but how do we phrase that? - Oct 8th 2010, 12:28 AMBobP
Am I misreading this ?

(for example) is not greater than or equal to 2. - Oct 8th 2010, 02:36 AMLukybear
Hm... i gues question is wrong then. Thxs